ANALYSIS OF THE CRIMINAL LIABILITY OF FANDI AS A CREW MEMBER WHO CLAIMS TO HAVE NO KNOWLEDGE OF THE NARCOTICS CARGO IN LIGHT OF LAW NUMBER 35 OF 2009 ON NARCOTICS - Hasiholan Sihaloho; Faisal Santiago (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
This study analyzes the criminal liability of Fandi as a crew member (Anak Buah Kapal / ABK) who claims to have had no knowledge of the presence of narcotics cargo, reviewed under Law Number 35 of 2009 on Narcotics and the general principles of Indonesian criminal law. The problem focuses on the construction of criminal liability and the relevance of the element of fault (mens rea), particularly intent (dolus/opzet) and negligence (culpa), in determining whether Fandi can be held criminally responsible. This research employs a qualitative method with a normative legal approach (doctrinal legal research), utilizing a statute approach, conceptual approach, and a complementary case approach. Legal materials are analyzed qualitatively through grammatical, systematic, and teleological interpretation, as well as deductive legal reasoning. The findings indicate that Fandi’s presence on board a vessel transporting narcotics does not automatically fulfill the elements of a criminal offense without proof of the subjective element. The principle of geen straf zonder schuld (no punishment without fault) affirms that criminal punishment requires legally and convincingly proven culpability. In the context of the subordinate position of a crew member, the analysis must consider authority, access to information, and control over the ship’s cargo. In the absence of evidence of knowledge, conscious cooperation, or significant violation of the standard of due care, criminal liability cannot be imposed. Therefore, the application of the Narcotics Law must be carried out proportionally to maintain a balance between the effectiveness of narcotics eradication and substantive justice.